APLIKASI CARA VOLTAMETRI PELEPASAN ANOOIK UNTUK ANALISIS LOGAM BERAT OALAM PARTIKULAT OARI UOARA - Evita Boes (Research Center for Chemistry - LIPI, 1991)
Determination of heavy metals such as Cu, Pb, Cd and Zn in airparticulate samples have been conducted by using Anodic Stripping Voltammerry method (ASV). Flow injection and wall-jet detector were supplemented to the ASV to improve the sensitivity and reproducibility of the mercury-film electrodes used. The air particulate samples analysed were taken with flow rate of 1 m3/minute. From 5 different places, 20 air samples were analysed and concentration of Cu, Pb, Cd; Zn between 0.0486-16.660 #gjm3 in airparticulates were observed. Limit of detection of the method for Cu, Pb, Cd and Zn were 0.015; 0.020; 0.016; 0.03 ppb respectively. Calibration curves for each metal from 50-500 ppb were linear with correlation coefficient 0.98.